Excelling on Campus, Lagging in the Workplace: The Paradox of Gender Equality in Indonesia - Hendika Dwinanda Wicaksana; Surfian Rahmat AP; Syfa Amelia; Muhammad Haikal; Ahmad Prasetya Hady (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2025)
Despite significant advancements in women's higher education in Indonesia, where female enrolment now surpasses that of men, major gender disparities persist in the labor market. This paper investigates the enduring paradox of